Scope for biodiesel and bioactive compounds production in the diatom Nitzschia punctata. (15th September 2021) - Saranya, G.; Ramachandra, T.V.
Highlights: Examined biodiesel and bioactive compounds in diatoms under various trophic modes. Among trophic modes, the highest biomass (139 ± 3 mg/L) was in mixotrophic diatoms. Scanning electron microscopy reveals higher C (~48%) in mixotrophic cultivation. Higher proportions of palmitoleic acid (~18–29%) and oleic acid (~26–35%). Superior biodiesel quality with saturates and mono-unsaturates (C16–C18) up to 90%. Abstract: The isolated diatom Nitzschia punctata was subjected to different trophic modes - autotrophy, heterotrophy, and mixotrophy and evaluated variations in growth rate, morphology, biochemical composition, and fatty acid profiles of diatoms in response to different nutritional modes. Glucose was used as a nutrient source in hetero and mixotrophic cultivation. Significant morphological variations in mucilage (jelly) stalks were found in hetero- and mixotrophically grown diatoms. The biomass yield was highest in mixotrophic diatoms (139.16 ± 3 mg/L), followed by autotrophic (127.04 ± 4 mg/L) and heterotrophically grown diatoms (95.22 ± 3 mg/L). Confocal microscopy studies using Nile red revealed significant bright yellow-gold fluorescence dispersed intermittently along with the mucilage stalks of mixotrophic and heterotrophic diatom cultures. Fourier transform infra-red (FTIR) spectroscopic studies showed a sharp absorption peak in hetero- and mixotrophic cultures at 1741 cm-1, indicating the presence of esters of fatty acids (R-C(O)-O-R). Elemental composition analysis using scanning electron microscopy revealed higher C (~48%) in mixotrophic cultivation. Fatty acid methyl esters (FAME) assessment through Gas chromatography and mass spectroscopy (GC–MS) showed higher proportions of palmitoleic acid (C16:1; ~18 – 29%) and oleic acid (C18:1; ~26 – 35%) with saturates and monounsaturates of C16 – C18 up to 90%, confirming of superior biodiesel quality property, which is desirable. The presence of Eicosapentaenoic acid (EPA) in hetero- and mixotrophic cultivation proves the scope for its potential utilisation as a source of bioactive compounds for industrial application.